2004
DOI: 10.1177/0037549704050918
|View full text |Cite
|
Sign up to set email alerts
|

Forest Fire Spread and Suppression in DEVS

Abstract: In this article, the authors discuss modeling and simulation of forest fire spread and suppression using the discrete event system specification (DEVS) cell space approach in DEVSJAVA. The event-based modeling approach enables efficient simulation of cell space and allows one to obtain timely simulation-based predictions of forest fire spread and suppression in uniform and nonuniform environmental conditions. This model represents an advance toward developing a real-time decision support simulation system for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 12 publications
1
40
0
Order By: Relevance
“…The concept of aggregate model complexity (i.e., composition complexity) is especially relevant for multimodeling approaches that have been under development for engineered systems and, to a lesser extent, for socioecological systems. In some cases (e.g., agent/cellular DEVS (Ntaimo et al 2004)), the complexity of hybrid model development may be explained in terms of both a modeling approach and the software toolkit. With an emphasis on the composition of models, this paper's focus is aggregate model complexity and choosing a model composition approach that helps to manage it.…”
Section: Composition Complexitymentioning
confidence: 99%
“…The concept of aggregate model complexity (i.e., composition complexity) is especially relevant for multimodeling approaches that have been under development for engineered systems and, to a lesser extent, for socioecological systems. In some cases (e.g., agent/cellular DEVS (Ntaimo et al 2004)), the complexity of hybrid model development may be explained in terms of both a modeling approach and the software toolkit. With an emphasis on the composition of models, this paper's focus is aggregate model complexity and choosing a model composition approach that helps to manage it.…”
Section: Composition Complexitymentioning
confidence: 99%
“…Cell-DEVS is a variant of DEVS (Discrete-Event Systems specifications), a modeling and simulation formalism that provides a mathematical representation of discrete-event systems [7]. Numerous studies have showed that DEVS is suited for the simulation of fire spread (including [8,9] and numerous others). Cell-DEVS is also widely used for this purpose thanks to its natural support for spatial relations and explicit timing constructions [ 2,5,10].…”
Section: Fire Modelmentioning
confidence: 99%
“…Then a complex application DEVSFIRE [20] is tested and the output result is presented. Both two simulations (also including simulations in the next sub-section) were conducted on a Dell Server P6600 with 8 Intel® Xeon™ MP 2.80GHZ processors, 7.50G memory, and Windows 2003 OS running DEVS C++ version.…”
Section: Experiments Verification For Algorithmmentioning
confidence: 99%